Corporate Governance and Strategic Leadership in Family Based Multinational Entrepreneurial Firms of India - Aranha, Nanditha Maria Alicia (2006)
Corporate Governance and Strategic Leadership have always been identified as key performance indicators in the corporate world. Family Based Entrepreneurial Businesses are regarded as one of the most important forms of organization, which has long been dominating the world economy. These businesses are the norms, and a major contributor to the GDP of the Indian economy. Corporate Governance is the new business mantra acclaimed world-wide. In India, this field is gaining momentum, and is being integrated into core business values and operations, as the framework for the implementation of sustainable development.